Interplays between nature's contributions to people, values of nature, and emotions expressed by smallholder farmers in Kilimanjaro, Tanzania: insights for inclusive conservation_Dataset - Sanya Julius, John; Pearson, Jasmine; Mwampamba, Tuyeni H.; Sesabo, Jennifer Kasanda; Martín-López, Berta (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
The dataset entails data frames from transcripts of 26 interviews conducted through the photovoice method with smallholder farmers at Mount Kilimanjaro, Tanzania, to understand how smallholder farmers in Kilimanjaro benefit from, value, and emotionally connect with nature. Additionally, the photovoice method included a transect walk with a photo taking exercise that included 84 photos. Through the exercise, the authors were able to understand the interplays between the nature's contributions to people (NCP), the values of nature and the emotional connection with nature.
Interview
Other
Keywords: Chagga; Landwirt; Kleinbäuerliche Strukturen; Naturleistungen für den Menschen (NCP); Werte; Emotion; Bewertung; Naturschutz; Sozial-ökologisches System; Baumgarten; Gebirge; Ökosystem; Kilimandscharo; Tansania; Mensch-Natur-Interaktion; Chagga; Farmer; Smallholder Structures; Nature's Contributions to People (NCP); Values; Emotion; Valuation; Nature Conservation; Social-ecological System; Homegarden; Mountain; Ecosystem; Mount Kilimanjaro; Tanzania; Human-Nature Interaction